The contribution of Electrical Resistivity Tomography (ERT) in Alpine dynamics geomorphology: case studies from the Swiss Alps - Scapozza, Cristian; Laigre, Laetitia (Géomorphologie : relief, processus, environnement, 2014)
The Electrical Resistivity Tomography (ERT) is a method based on the study of the capacity of the subsurface to resist to an electrical current. The data processing based on forward and inverse modelling process allows obtaining tomographies of the electrical resistivities distribution in the ground. This helps to determine the nature of the subsurface, its rough porosity, the presence of water and/or ice and thus to characterise the environments of deposition. Three study cases were chosen in the Swiss Alps to illustrate the potentialities of this method for studying landforms in mountain dynamic environments: the first one concerns the study of permafrost distribution in a high altitude talus slope in the Valais Alps; the second one analyses the architecture of fluvial deposits in the Rhône River floodplain and the last one considers the geometry of the Cimadera landslide located in the Ticino Canton. Through these three study cases, some specific aspects concerning both the prospecting strategy of complex and heterogeneous landforms and the interpretation, namely modelling based on conceptual models, are highlighted and lead to formulate some recommendations when using this method. La Tomographie des Résistivités Electriques (TRE) est basée sur l’étude de la capacité des formations superficielles à s’opposer au passage d’un courant électrique. L’élaboration des données basée sur des processus de modélisation directe et inverse consent d’obtenir des tomographies de la répartition des résistivités électriques dans le sous-sol, permettant de déterminer la nature de la sub-surface, la porosité des formations, la présence d’eau et/ou de glace et, à partir de là, de pouvoir caractériser les milieux de sédimentation. Trois cas d’étude ont été choisis dans les Alpes suisses pour illustrer les potentialités de la méthode pour l’étude des formes dans des environnements dynamiques de montagne : le premier concerne l’étude de la répartition du pergélisol dans un éboulis de haute altitude situé dans les Alpes ...